Pattern and In-Hospital Mortality of Thoracoabdominal Injuries Associated with Motor Vehicle Accident-Related Head Injury: a Single-Center Retrospective Study - Walid M. Abd El Maksoud; Mubarak Ali Algahtany (Applied Bionics and Biomechanics)
Aim. To determine the pattern and in-hospital mortality of thoracoabdominal injuries associated with head injuries (HI) due to motor vehicle accidents. Settings and Design. A single-center retrospective study in a tertiary care hospital, level 1 trauma center in the southern region of Saudi Arabia. Methods and Materials. Descriptive analysis was conducted to evaluate sex, age, types of head injury, associated thoracoabdominal injuries, particular admission day, duration of hospital stay, and discharge category, and associations between different variables and outcomes were analyzed. Results. The cohort had a mean age of 26.9±15.8 years, with a predominance of men (86.9%). Thoracoabdominal injuries were present in 6.8% of MVA-related HI, and 14.3% of victims expired during their hospital stay, mostly within the first 10 days. All expired patients had posttraumatic brain lesions. Moreover, there was a significant association between intensive care unit (ICU) admission and poor prognosis. Conclusions. Existence of posttraumatic brain lesions and requirement of ICU admission are significant variables affecting outcomes in patients with motor vehicle-associated HI with concomitant thoracoabdominal trauma in this study. Patients who survived the first 10 days after trauma seemed to have a better prognosis. More efforts are needed to reduce the health burden of this lethal injury.